2016
DOI: 10.1371/journal.pone.0155991
|View full text |Cite
|
Sign up to set email alerts
|

The Corticofugal Effects of Auditory Cortex Microstimulation on Auditory Nerve and Superior Olivary Complex Responses Are Mediated via Alpha-9 Nicotinic Receptor Subunit

Abstract: Background and ObjectiveThe auditory efferent system is a complex network of descending pathways, which mainly originate in the primary auditory cortex and are directed to several auditory subcortical nuclei. These descending pathways are connected to olivocochlear neurons, which in turn make synapses with auditory nerve neurons and outer hair cells (OHC) of the cochlea. The olivocochlear function can be studied using contralateral acoustic stimulation, which suppresses auditory nerve and cochlear responses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Evidences in bats [34] and chinchillas [35, 36] have demonstrated that the inactivation and electrical stimulation of the auditory cortex can modulate cochlear responses in a frequency specific manner. In addition, Aedo et al [37] showed in the alpha-9 nicotinic receptor knock-out mice that these corticofugal effects are produced through the medial olivocochlear system.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences in bats [34] and chinchillas [35, 36] have demonstrated that the inactivation and electrical stimulation of the auditory cortex can modulate cochlear responses in a frequency specific manner. In addition, Aedo et al [37] showed in the alpha-9 nicotinic receptor knock-out mice that these corticofugal effects are produced through the medial olivocochlear system.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory efferent system is a neural network that comprises descending projections from the auditory cortex to the inferior colliculus, cochlear nucleus and superior olivary complex 10 12 , from where the medial olivocochlear (MOC) bundle emerges making synapses directly with outer hair cells of the cochlea 13 . The functionality of these corticofugal pathways has been demonstrated in bats, chinchillas and humans 14 17 , and these descending projections are proposed to be the mediators of selective attention top-down effects on the cochlear receptor 18 , 19 . In addition, peripheral modulations of the cochlear receptor during visual attention have been demonstrated in humans 20 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase of early incorrect responses could be indicative of more impulsive decision in KO mice induced by auditory distraction in a visual selective attention task. Auditory-cortex descending pathways can be though as a neural circuit that allows top-down filtering of afferent auditory responses (Xiao and Suga, 2002 ; León et al, 2012 ; Aedo et al, 2016 ). In that line, we propose that the increased auditory distraction in KO mice could be consequence of the lack of OHC inhibition by MOC synapses in the KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In that line, we propose that the increased auditory distraction in KO mice could be consequence of the lack of OHC inhibition by MOC synapses in the KO mice. This might impair the filtering of auditory distractors by the corticofugal projections from the auditory cortex that modulate MOC neurons (Dragicevic et al, 2015 ; Aedo et al, 2016 ). Importantly, auditory thresholds and supra-thresholds ABR amplitudes were similar for WT and KO mice, and only a significant difference in the latency of wave V was obtained.…”
Section: Discussionmentioning
confidence: 99%